Rollers Vibration of Pipe Conveyor - Klimenda, Frantisek; Skocilasova, Blanka (Manufacturing Technology Journal, 2015)
This article is deals of noise and vibration measurement of rollers for belt conveyor. In the first part of article a stand measuring is described and individual rollers types which were measured. There are five types of rollers for measurement. The first type are the Transroll rollers which were measured with the rubber pads. The second type are the Transroll rollers again. The third type are the Sandvik rollers and the fourth type are "Italian" rollers. Process of noise and vibration measurement of the individual rollers types is given. In conclusion of this article is noise and vibration measurement evaluation. Compared of the Transroll roller with pad and without pads is given. Three the highest acceleration values in depending on the frequency of vibration in individual directions (x, y, z) are given.
Keywords: Belt conveyor; Roller; Vibration; Noise